New Thoughts on Formation of Tourism Perceived Images: An Investigation of Guangxi’s Overseas Chinese Students from ASEAN - Luo, Tianyang; Mohamed, Ahmad Edwin; Yusof, Noor Suhaila (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The research attempts to explain the psychological formation of the image of the sojourn by overseas students who are culturally homogeneous with the sojourn by constructing a comprehensive framework for the composition of the perceived image that contains the new dimension of cultural attachment. In particular, a group of 482 overseas Chinese students from ASEAN with learning experience in Guangxi are the respondents, benefiting from the deep ties between their ethnic and cultural backgrounds with mainland China. It is a strategic consideration based on Guangxi’s international tourism market and image promotion for ASEAN. The research uses quantitative analysis to combine the external influences previously supported in the literature, cultural attachment, and Cognitive-Affective-Conative (CAC) three-dimensional perceived image framework into a more comprehensive model to conduct a hypothetical-deductive study. The results of the quantitative analysis consolidate to a certain extent that the internal constitutive conditions of perceived image are promoted by the CAC model and further test the influence of perceived image under the combined effect of internal and external factors. Meanwhile, it is confirmed that cultural attachment has a strong role in the formation of the perceived image of a specific tourist group. The overall conclusions of the research are rich in academic significance and represent a theoretical expansion of the destination marketing system in response to real-world needs.